Relationship between procedure and result indicators during a football season in the five major European leagues - Daniel Ramos Pérez; Julen Castellano; Antonio Hernández-Mendo (Federación Extremeña de Balonmano; University of Extremadura, 2021)
The aim of this paper is to find out the relationship between the procedure indicators and result (goals scored and points accumulated) by each of the teams in male elite football. To this end, we have analyzed the performance of the five major European leagues during the 2018-19 season (98 teams and 3,652 performances). Different Performance Indicators (IR) have been employed: a) the result indicators: goals scored and received, and points obtained; b) the Procedure Indicators (IP): b1) for the offensive finishing phase: shots, centers, key passes and scoring first; b2) for the creation attack phase: the passes attempted and performed, and ball possession (%), and b3) in the defensive phase: recoveries and fouls committed in Zones 4-5 of the field. A multiple regression analysis explained 83.2% of the variance in the relationship between points and the predictor variables, as well as 82.9% of the number of goals scored. The main results of the study show that in the Spanish league the goals correlate less with the accumulated points and ball possession, number of key passes and scoring first are the variables that most correlate with the accumulation of goals and points at the end of the season. Keywords: match analysis; performance indicator; team sport; success